Karakterisasi Fisik Pati Tapioka Modifikasi Gabungan Hidroksipropilasi dengan Fosfat-Ikat Silang - Didah Nur Faridah; Ali Thonthowi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
Native tapioca starch has a weakness in its functional properties which causes limited use of starch as a food ingredient. This weakness can be overcome by applied double modifications with hydroxypropylation and cross-linking processes. The hydroxypropylation was applied using various concentrations of propylene oxide (8, 10, and 12%), then followed by crosslinking modifications using a combination of STPP (Sodium tripolyphosphate) and STMP (sodium phosphate) with a ratio of 2%: 5%. The results of the double modification can changed the physical and chemical characteristics of starch. These changes include the gelatinization temperature of modified tapioca starch (66.00 – 68.00 oC) which is lower than the natural starch (68.45 oC). The peak viscosity of modified tapioca starch (> 5735 cP) was higher than the original starch (5635 cP) with the viscosity setback was also higher (3136-3564 cP) than the original starch (1192 cP). Modified starch has a lower viscosity decrease value (698-1530 cP) than the original starch (4089 cP). Double modified tapioca starch has heat-resistant and stirring properties